Dietary supplementation with L-carnitine elevates intracellular carnitine levels and affects gene expression of SLC25A20 and COX4I1, as well as non-mitochondrial respiration of bovine blood cells during systemic immune challenge - Seemann, Leonie; Kersten, Susanne; Bühler, Susanne; Billenkamp, Fabian; Meyer, Ulrich; Visscher, Christian; Huber, Korinna; Most, Erika; Eder, Klaus; Dänicke, Sven; Frahm, Jana (Frontiers in Immunology, 2025)
L-carnitine plays a key role in shuttling free fatty acids from the cytosol into the mitochondrial matrix. Fatty acids, among other substrates, are utilized by immune cells as an energy source. Therefore, L-carnitine, which is authorized as a feed additive in cattle, may influence the metabolism of peripheral blood mononuclear cells (PBMC) during an immune challenge. To test this hypothesis, a feeding trial was conducted with 53 German Holstein cows, comprising a control group (CON, n = 26) and an L-carnitine supplemented group (CAR, n = 27, 25 g rumen-protected L-carnitine/cow/d). On day 111 after calving, all cows were intravenously injected with lipopolysaccharides (LPS, 0.5 µg/kg body weight as bolus injection, E. coli) to induce a systemic immune challenge. Blood samples were collected on day 143 ante injectionem (ai), day 11 ai, 24 hours post injectionem (pi), and day 14 pi and PBMC were isolated. The used methods included high-performance liquid chromatography coupled with mass spectrometry, Alamar Blue assay, real-time qPCR, and the Mito Stress Test of the Seahorse Analyzer (Agilent, Santa Clara, California, USA). L-carnitine supplementation significantly increased intracellular concentrations of carnitine and its precursor γ-butyrobetaine in PBMC of dairy cows. The gene expression of carnitine-acylcarnitine translocase (SLC25A20) in PBMC remained stable in CAR, whereas it was upregulated in CON during the LPS challenge, suggesting an adaptation to increased energy demands in CON. A contrasting pattern was detected for the gene expression of cytochrome c oxidase subunit 4I1 (COX4I1), with stable levels in CON and a downregulation in CAR due to LPS injection. However, most of the investigated genes were unaffected by L-carnitine supplementation, and responded significantly to LPS injection. The same applied for PBMC mitochondrial functionality and metabolic activity as assessed by ex vivo approaches, whereas non-mitochondrial respiration rate was significantly affected by L-carnitine supplementation over time. In conclusion, dietary L-carnitine supplementation of 25 g per cow per day led to a balanced distribution of carnitine and γ-butyrobetaine between bovine blood cells and plasma, but there were only minor effects on gene level and cellular respiration.